THE CONTINUITY OF CARE FROM THE PERSPECTIVE OF THE BEING CARED FOR - Letícia Fernanda Cota Freitas; Danielle de Araújo Moreira; Maria José Menezes Brito (Universidade Federal do Paraná, 2014)
This study aims to understand the continuity of the care from the perspective of companions, and service users with chronic non-communicable diseases. The research is qualitative and descriptive, and was undertaken in 2012 in an Emergency Department of the municipality of Betim in the Brazilian state of Minas Gerais, with seven participants. The information was collected through semistructured interviews. Three categories emerged from the analysis undertaken: Informational continuity and the impasses to achieving continuity of care; Managerial continuity: weaknesses which affect the continuity of the care; Meanings of the continuity, for the being cared for: positive aspects which permeate the routine actions. Weaknesses were observed in the continuity of the care for the patients with chronic complaints, caused by failures in communication, inadequate interaction between the services of the care network, and inadequate managing of the service. It is considered essential to outline strategies which aim to overcome limitations so as to ensure comprehensive and resolutive care.